THE IMPLEMENTATION OF SPEAK ENGLISH WITH ME PROGRAM ON SPEAKING ABILITY OF STUDENTS OF ENGLISH COURSE AT UPT BAHASA OF IBI DARMAJAYA IN THE ACADEMIC YEAR OF 2014/2015 - Magdalena, Betty (Prosiding International conference on Information Technology and Business (ICITB), 2015)
This research is aimed at knowing the implementation ofSpeak English with Me program toward speakingability of students of English course at UPT Bahasa of IBIDarmajaya. This research uses random samplingtechnique where there are 50 out of 685 students ofElementary English 2 (level 2) taken as the sample. In theresearch, there are two kinds of tool used to collect thedata; they are questionnaire and documentation. Theresult of the research shows that Speak English with Meprogram can be implemented to improve speaking abilityof students of English course at UPT Bahasa of IBIDasrmajaya.KEY WORDS: Implementation, Speak English with Me , Englishcourse